Environmentally Friendly Flame-Retardant and Its Application in Rigid Polyurethane Foam - Yongjun Chen; Zhixin Jia; Yuanfang Luo; Demin Jia; Bin Li (International Journal of Polymer Science)
A novel Flame-Retardant N-(P,P′-diphenyl) phosphorus-based-(3-triethoxysilicon) propylamine (DPTP) was synthesized in this study. The impact of DPTP on the mechanical properties, thermal stability, and flame retardancy of rigid polyurethane foam (RPUF) was studied. The addition of DPTP to RPUF can significantly reduce the undesirable thermal effects and smoke density during combustion, as well as increasing the limiting oxygen index. Compared with pure RPUF, the peak heat release rate of RPUF containing 10 phr of DPTP decreased by 39.4%, while its peak smoke production rate decreased by 49.9%. However, it was also found that the addition of DPTP reduced the compressive strength of RPUF.